G291(P) Bruising in children: Accidental, inflicted or medical illness?. (27th April 2016) - Datta, V; Heaf, E; Khan, M; Date, A
Abstract : Introduction: Minor accidental injuries are the commonest cause of bruises in children. Bruises can also signal an underlying medical illness or an inflicted injury. Confirming maltreatment and assessing bruises in this context can be challenging for clinicians. Case Summary: We present the case of a 4 year old girl who presented with an unexplained big bruise with an underlying swelling over the right upper arm. Due to delayed presentation and unexplained bruising concerns were raised with regards to non-accidental injury. Further history revealed bruising in the same area few months ago. She did not have bruises anywhere else on the body. The family was not known previously to social services and other than the unexplained nature of the bruising no other obvious safeguarding concerns were identified in the history. The delayed presentation was explained satisfactorily. However the recurrent bruising in the same area did raise concerns regarding possible underlying structural lesion. Investigations: X ray of right arm, Full blood count, coagulation profile, Protein C, S, and Factor v Leiden were all normal. Ultra sound of the lesion showed presence of haematoma under the bruise. Ultrasound Doppler scan was performed which revealed an underlying veno-lymphatic malformation which is a rare cause of bruising. Conclusion: This case highlights the challenges associated with the diagnosis of an unexplained bruising. Though Non accidental injury must always be considered in such cases, medical professionals should be aware of other rare medical conditions which simulate inflicted injuries. This would help in initiating appropriate management plan and serious consequences associated with the wrong diagnosis of non-accidental injury can be avoided.